DEIKSIS PERSONA DALAM FILM DUA GARIS BIRU KARYA GINA S. NOER PRODUKSI STARVISION DAN WAHANA KREATOR - Nida Fahrunisa; Asep Purwo Yudi Utomo (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2020)
Person deixis can be found in various speeches, both located in everyday speech and dialogue between characters in a film, including Dua Garis Biru. This study aims to classify and analyze the kinds of person deixis and their functions in the movie Dua Garis Biru. This study used descriptive qualitative method. The data analysis in this study used a pragmatic approach. They are collecting data using the observation method with note-taking techniques. The results showed that the types of personal deixis used in the film Dua Garis Biru are single and plural form. They are singular and plural first person deixis, singular and plural second-person deixis, and third single and plural third person deixis. Each type of person deixis has a different function according to its context and reference. The singular first-person deixis is saya, aku (English: I/me),gue and gua (English:I/me in informal style),-ku (English: my). The first person deixis in the plural is kita and kami (English: we/us). The single second person deixis used in the film Dua Garis Biru is kamu (English: you), -mu (English: your), loe and lu (English: you), while the second person plural deixis is kalian (English: you). The third person deixis consists of singular third-person deixis, namely he/her or his/her, and the plural third-person deixis, namely they/their/them and everybody. The use of deixis is influenced by familiarity, age, social status, and speech situation.